The Rwanda Crisis : An Analysis of News Magazine Coverage - Wall, Melissa A. (Gazette (Leiden, Netherlands), 1997)
American media traditionally have created one-dimensional portraits of intracountry conflict in Africa. Worldwide changes since the end of the Cold War have given many media observers hope that African violence might be covered more insightfully. To see whether this was true, news magazine coverage of the 1994 Rwanda crisis was analyzed. Findings suggest that some patterns such as viewing African events through an East-West frame have disappeared, but other types of simplification prevail.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8wMDE2NTQ5Mjk3MDU5MDAyMDAz